Strategic Intellectual Property Rights Policy and North-South Technology Transfer - Alireza Naghavi (Fondazione Eni Enrico Mattei (FEEM), 2005)
This paper analyzes welfare implications of protecting intellectual property rights (IPR) in the framework of TRIPS for developing countries (South) through its impact on innovation, market structure and technology transfer. In a North-South trade environment, the South sets its IPR policy strategically to manipulate multinationals decisions on innovation and location. Firms can protect their technology by exporting or risk spillovers by undertaking FDI to avoid tariffs. A stringent IPR regime is always optimal for the South as it triggers technology transfer by inducing FDI in less R&D-intensive industries and stimulates innovation by pushing multinationals to deter entry in high-technology sectors.
Keywords: O34; F23; F13; L13; O32; L11; O38; 330; Intellectual property rights; Technology transfer; Multinational firms; Foreign direct investment; North-South trade; Immaterialgüterrechte; Technologietransfer; Nord-Süd-Beziehungen; Direktinvestition; Multinationales Unternehmen; Theorie